Prispevek k poznavanju podzemeljske favne hroščev v Šentanskem rudniku - Kofler, Bojan (Acta entomologica slovenica (Ljubljana), 2005)
Results of a three year survey of the hypogean beetles in the mine Šentanski rudnik near Podljubelj (northern part of Slovenia) are presented. Four species were found and the species Anophthalmus pretneri pretneri is new to the fauna of this mine.
Keywords: Coleoptera; favna; hrošči; podzemeljska favna; Šentanski rudnik